Recent progress in epitaxial growth of two‐dimensional phosphorus. (3rd August 2021) - Wang, Yihe; Sun, Shuo; Zhang, Jialin; Huang, Yu Li; Chen, Wei
Abstract: Phosphorus is an important non‐metal element with many allotropes and tunable electronic properties. As one of the most important allotropes of phosphorus, two‐dimensional (2D) black phosphorus (BP) possesses many extraordinary properties, such as high charge carrier mobility with high on/off ratio, thickness‐dependent direct bandgap varying from 0.3 to 2 eV, and anisotropic electrical, optical and thermal properties. Inspiring by the success of 2D BP, other 2D phosphorus allotropes with intriguing properties for next‐generation electronic and optoelectronic devices have also attracted much attention. However, large‐scale growth of high‐quality 2D single/few‐layer phosphorus remains a great challenge. In this review, we highlight recent progress achieved on 2D phosphorus, with special focus on the epitaxial growth of 2D BP films, blue phosphorus (BlueP) monolayers as well as phosphorus‐metal porous networks. The remaining challenges and future perspectives on the development of monolayer phosphorus or phosphorus‐metal alloys are also provided. Abstract : In this study, we highlight recent progress achieved on two‐dimensional (2D) phosphorus, with special focus on the epitaxial growth of 2D BP films, BlueP monolayers as well as phosphorus‐metal porous networks. The remaining challenges and future perspectives on the development of monolayer phosphorus or phosphorus‐metal alloys are also provided.